Constraining scope ambiguity in LFG+glue - Gotham, M (CSLI Publications, 2020)
A major strength of the Glue approach to semantic composition for LFG is that it accounts for quantifier scope ambiguity without the need for additional assumptions. However, quantifier scope is more rigid in some languages and constructions than Glue would lead us to expect. I propose a mechanism for constraining scope ambiguity in LFG+Glue, based on ideas taken from Abstract Categorial Grammar. Unlike existing proposals, this account does not depend on representational constraints on linear logic derivations or meaning representations.